Facilities for automation of development of parallel programs on the basis of ontologies and algebra of algorithms - Doroshenko, A.Yu.; Yatsenko, E.A. (PROBLEMS IN PROGRAMMING, 2026)
An approach to formalized development of parallel programs using ontologies and algebra-algorithmic facilities is proposed. Ontology gives opportunity to describe the skeleton of the program representing main objects in the given subject domain – data, functions and relations between functions. Once the skeleton of the program has been built, further development can be done in automated manner with the Integrated toolkit for Design and Synthesis developed by the authors, which is based on using algorithmic algebras facilities. The application of the approach is illustrated with an example of developing parallel MPI program in the subject domain of sorting algorithms.Problems in programming 2008; 4: 94-103